Studi Kasus pada Ibu Hamil Trimester III dengan Anemia - Safinatunnaja, Bq; Abdiani, Baiq Tuhu; Hidayati, Kurnia (PT.Mantaya Idea Batara, 2024)
A lack of erythrocytes (red blood cells) in the blood which causes a lack of oxygen in the tissues is a body condition called anemia. Anemia pregnancy is very dangerous for the mother and fetus, because it can result in abortion, bleeding, premature birth, fetal growth retardation and infection. This research uses a descriptive method with a case study approach. The research subjects in this case study were pregnant women who experienced mild anemia in the Labuapi Health Center working area. This case describes obstetrical care in a pregnancy with anemia. The results of this case study, there was an enhancement in hemoglobin in pregnant women who were given prenatal care for 2 weeks. At the initial visit the respondent's hemoglobin (Hb) was 10.3 gr/dl. On the second visit hemoglobin (Hb) increased by 10.9 gr/dl and on the third visit the respondent's Hb became 11.2 gr/dl. Providing comprehensive care to pregnant women with anemia for 2 weeks can increase Hb in respondents. The care provided includes counseling about anemia in pregnancy, providing IEC on how to increase Hb by encouraging mothers not to stay up late, consuming a balanced nutritional intake high in iron and giving 2 FE tablets per day. The conclusion of this study is that there was an enhancement in hemoglobin from 10.3 gr/dl to 11.2 gr/dl after being given midwifery care to pregnant women with anemia for 2 (two) weeks